2005
DOI: 10.1039/b510245f
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of melting of CCl4 in carbon nanotubes

Abstract: We report dielectric relaxation spectroscopy measurements of the melting point of carbon tetrachloride confined within open-tip multi-walled carbon nanotubes with two different pore diameters, 4.0 and 2.8 nm. In both cases, a single transition temperature well above the bulk melting point was obtained for confined CCl4. These results contrast with what was obtained in our previous measurements using carbon nanotubes with a pore diameter of 5.0 nm, where multiple transition temperatures both above and below the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…The shorter component of the relaxation time is of the order of 10 −5 s and can characterize the Debye relaxation of the liquid C 6 H 5 Br in the pores. Molecular simulation results for CCl 4 in MWNTs of (2.8 and 4) nm diameter show that before the melting temperature all adsorbate regions behave as dense, liquid-like fluids with short-range positional and bond orientational order, so the branch of relaxation time of the order of 10 −5 s, which is much lower than for the bulk liquid, can be related to the adsorbate. In the temperature region (271 to 243) K, we still observe the branch of relaxation time related to MWS polarization and a branch with relaxation time values similar for the crystal C 6 H 5 Br phase.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The shorter component of the relaxation time is of the order of 10 −5 s and can characterize the Debye relaxation of the liquid C 6 H 5 Br in the pores. Molecular simulation results for CCl 4 in MWNTs of (2.8 and 4) nm diameter show that before the melting temperature all adsorbate regions behave as dense, liquid-like fluids with short-range positional and bond orientational order, so the branch of relaxation time of the order of 10 −5 s, which is much lower than for the bulk liquid, can be related to the adsorbate. In the temperature region (271 to 243) K, we still observe the branch of relaxation time related to MWS polarization and a branch with relaxation time values similar for the crystal C 6 H 5 Br phase.…”
Section: Resultsmentioning
confidence: 98%
“…Simulation and experimental studies have shown that an elevation in the melting point is observed for systems where the adsorbate-wall interactions are strong compared to the adsorbate-adsorbate interactions. 1,[3][4][5][6][7][8][9][10]14 MWNTs are representative of materials with strongly attractive cylindrical pores. This effect of the pore size has been observed in previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] of strongly attractive pores with cylindrical geometry and has been explained as follows: the adsorbate-wall attractive interactions dominate the phase behavior at the smaller pore diameters, leading to larger increases in the solidification temperatures of the molecular layers close to the walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many simulation studies have suggested that, when pore walls are crystalline, the strength of the fluid–wall interaction relative to the fluid–fluid interaction plays a very important role in determining the freezing and melting temperatures as well as the structure of the confined fluid. Indeed, in a model carbon pore of cylindrical shape, freezing-point elevation has been observed, as opposed to the general observations of freezing-point depression of a confined liquid in amorphous silica pores. , So far, however, experimental verification of such a prediction was extremely difficult because it was not easy to obtain mesoporous materials with crystalline walls. Carbon nanotubes possess two types of pores, outside and inside of the nanotubes, and thus the interpretation of the obtained results is always accompanied by great difficulty in discrimination of two components condensed in these pores. , Very recently, we have shown that, for the Kr confined in the crystalline pores of ordered mesoporous carbon, freezing and melting take place almost reversibly, in sharp contrast with that in the amorphous pores of mesoporous silica . For the liquid Kr confined in the crystalline carbon pores, crystalline bilayer film that is commensurate with the bulk structure of the confined solid Kr is already in place at a boundary between the liquid and the carbon pore walls at the equilibrium freezing point and thus plays a role as a critical nucleus in freezing of the interior phase, leading to the lack of hysteresis between freezing and melting for the Kr confined in the crystalline carbon pores .…”
Section: Introductionmentioning
confidence: 97%
“…Carbon nanotubes possess two types of pores, outside and inside of the nanotubes, and thus the interpretation of the obtained results is always accompanied by great difficulty in discrimination of two components condensed in these pores. 34,35 Very recently, we have shown that, for the Kr confined in the crystalline pores of ordered mesoporous carbon, freezing and melting take place almost reversibly, in sharp contrast with that in the amorphous pores of mesoporous silica. 36 For the liquid Kr confined in the crystalline carbon pores, crystalline bilayer film that is commensurate with the bulk structure of the confined solid Kr is already in place at a boundary between the liquid and the carbon pore walls at the equilibrium freezing point and thus plays a role as a critical nucleus in freezing of the interior phase, leading to the lack of hysteresis between freezing and melting for the Kr confined in the crystalline carbon pores.…”
Section: Introductionmentioning
confidence: 99%